2007
DOI: 10.1089/scd.2007.9991
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Enlivenment of Blood Flow Recovery Following Endothelial Progenitor Cell Transplantation into Ischemic Hindlimb

Abstract: Nicotine has been demonstrated to stimulate postnatal angiogenesis, having an antiapoptotic effect on endothelial cells. Given the extent of this angiogenesis-promoting effect, we hypothesized that nicotine may also stimulate postnatal vasculogenesis on endothelial progenitor cells (EPCs). Our analyses reveal some intriguing results using an in vitro assay with 2 x 10(-6) M of nicotine (smoker's average nicotine concentration and the dose of nicotine replacement therapy). The proliferation and migration activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…EPC dysfunction is common in chronic smokers, but increasing evidence suggests that short-term nicotine exposure presents benefits to EPCs (12). In the present study, the long-term effects of nicotine on EPCs were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPC dysfunction is common in chronic smokers, but increasing evidence suggests that short-term nicotine exposure presents benefits to EPCs (12). In the present study, the long-term effects of nicotine on EPCs were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (11) reported that low concentrations of nicotine increase the EPC count and their proliferative, migratory, adhesive and vasculogenic capacity. Furthermore, nicotine administration improved the blood flow in a rat ischemic hindlimb model by enhancing the function of transplanted EPCs (12). A hypothesized explanation of these effects was that nicotine reduced EPC senescence by activating telomerase through the PI3K/Akt pathway (13).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a direct antiapoptotic effect of nicotine, when added to EPC culture media, was demonstrated. In an ischemic hindlimb model, nicotine treatment of early outgrowth EPC transplanted mice improved blood flow recovery in comparison to transplantation of EPC alone [87].…”
Section: Smokingmentioning
confidence: 94%
“…Nicotine has been demonstrated to stimulate postnatal angiogenesis, having an antiapoptotic effect on endothelial cells. It was observed that nicotine stimulated postnatal vasculogenesis on endothelial progenitor cells (EPCs) [75]. The effect of nicotine on EPC survival was significantly enhanced under serum starvation.…”
Section: Nachrs and Tumor Angiogenesismentioning
confidence: 99%
“…The effect of nicotine on EPC survival was significantly enhanced under serum starvation. Furthermore, the antiapoptotic effect of nicotine was blocked completely by nicotinic acetylcholine receptor (nAChR) antagonist hexamethonium bromide [75]. …”
Section: Nachrs and Tumor Angiogenesismentioning
confidence: 99%